FOXO3 as a new IKK-ε-controlled check-point of regulation of IFN-β expression. - Luron, L; Saliba, D; Blazek, K; Lanfrancotti, A; Udalova, I (2012)
Cell survival transcription factor FOXO3 has been recently implicated in moderating pro-inflammatory cytokine production by dendritic cells (DCs), but the molecular mechanisms are unclear. It was suggested that FOXO3 could antagonize NF-κB activity, while IKK-β was demonstrated to inactivate FOXO3, suggesting a cross-talk between the two pathways. Therefore, FOXO3 activity must be tightly regulated to allow for an appropriate inflammatory response. Here, we show that in human monocyte-derived DCs (MDDCs), FOXO3 is able to antagonize signaling intermediates downstream of the Toll-like receptor (TLR) 4, such as NF-κB and interferon regulatory factors (IRFs), resulting in inhibition of interferon (IFN)-β expression. We also demonstrate that the activity of FOXO3 itself is regulated by IKK-ε, a kinase involved in IFN-β production, which phosphorylates and inactivates FOXO3 in response to TLR4 agonists. Thus, we identify FOXO3 as a new IKK-ε-controlled check-point of IRF activation and regulation of IFN-β expression, providing new insight into the role of FOXO3 in immune response control.